El estudio de la magia en la Antigüedad tardía: Algunas consideraciones prácticas - Torijano, Pablo A. (Gerión. Revista de Historia Antigua, 2000)
This article takes a look at the approaches to the study of magic in Late Antiquity. The partial analysis of a magical figure (King Solomon) makes possible to extract new indications for a better understanding of magic and its role in the Mediterranean oikoumene, and suggests the necessity of a better categorization of the magical disciplines. These indications should be taken into account for the study of magic and magical mentality in any cultural setting of Late Antiquity.